Teknik Pengujian Equivalents Partitioning pada Aplikasi Sistem Pendaftaran PAUD berbasis WEB dengan Menggunakan Black Box - Mauludin Yusup Suyudi; Adinda Putriani Pratiwi; Rachell Fauziah Mawahdah; Yuda Andika Purwara; Irpan Kusyadi (Teknik Informatika Universitas Pamulang, 2020)
Testing is the most important thing to produce a system that is very good and also useful. Pengban a system must be carried out because if there is no prior testing of a system, then what will happen to the system will get a system error that results in a poor quality system and will result in a loss for developers and users. Experiments that have been carried out can find an error, disability, or failure on a system that has been known from the beginning and immediately corrected more thoroughly. In the test there are also types of system experiments, one of which is by testing the black box using an equivalent method that is good for looking for an error on the system. The equivalent method can break down the input domains of the program into a class that can solve test cases. Based on the results of a test that has been done, this application still has an error and also a defect in a system.